Recoilless Gun System as a Particular Formof General Interior Ballistics Model of Gun Propellant Systems - Zbigniew SURMA; Zbigniew SURMA (Układ bezodrzutowy jako szczególna postać uogólnionego modelu balistyki wewnętrznej lufowych układów miotających, 2018)
The development of the interior ballistics general model of gun propellant systems by taking into account the specificity of the recoilless propellant system is presented in this paper. The presented expanded physical and mathematical model makes possible the simulation of classical and nonclassical gun systems: two-chamber, mortar, and the considered recoilless one. To solve the system of equations associated with the mathematical model, a computer programme was developed. An analysis was made for two configurations of a recoilless system, differing in the way of arrangement of a propellant charge, i.e., with the propellant charge moving together with a projectile and with the propellant charge burning in a cartridge chamber. The obtained calculation results showed that the system, in which the propellant charge moves together with a projectile, has the maximum pressure and the muzzle velocity higher in comparison with the system with the propellant charge burning in a cartridge chamber. Influence of a way of placement of the propellant charge is the stronger, the higher is the ratio of its mass to the projectile mass. The results of the accomplished calculations, especially the pressure inside the barrel as well as motion parameters of the projectile make the grounds for projecting and construction optimization of the recoilless gun systems.
Keywords: Balistyka wewnętrzna- modelowanie pracy układów miotających; Balistyka wewnętrzna- modelowanie pracy układów miotających